The feasibility of implementing an injury prevention program in high school basketball players - Silkman, C. S.; McKeon, J. M.; McKeon, P. O.; Mattacola, C. G.; Lattermann, C. (Journal of Athletic Training, 2012)
Context: In rural and low-income areas, access to health care is limited and injury prevention programs are not readily available. Balance training has been shown to reduce ankle and knee injuries under the supervision of a healthcare professional, however, little is known about what can be done to prevent injuries in these underserved locations. Objective: To determine the feasibility of implementing an injury prevention program for boys and girls basketball teams at rural, underserved Kentucky high schools. Design: Cohort study. Setting: Fieldtesting. Patients or Other Participants: Four rural interscholastic high school basketball teams in Kentucky that included 2 boy`s teams (Team A n=19, Team B n=11), 2 girls teams (Team C n=18, Team D n=9) and 4 coaches 2 males (Teams A, B) and 2 females (Teams C and D). Interventions: Each coach was given an injury prevention program that utilized evidence-based exercises. Coaches were provided with exercise descriptions and a video demonstrating each exercise. An athletic trainer instructed coaches on proper technique and commonly made errors. Coaches were instructed to implement the exercise program three times per week throughout the course of the season. A log of practice, games, and exercise sessions was documented by the coaches and submitted once a week. Single-limb postural control was assessed pre- and post-intervention using measures of Time-to-Boundary (TTB). Each subject was tested bilaterally for 3 trials of 10s and the mean was taken for each limb. Main Outcome Measures: The dependent variables were the compliance rate to complete the exercise program three times per week, percentage of subjects that drop-out and TTB measures. Compliance was calculated by number of sessions completed divided by number of sessions proposed. Acceptable compliance was set at 90% a priori. T-tests were used to measure the differences in TTB pre to post for each team. Results: Overall, the compliance rate was 65%± 0.10. Team C met adequate compliance levels at 96%± 0.10, while Teams A, B, and D resulted in unacceptable compliance rates 53%± 0.20, 49%± 0.30, and 88%± 0.20 respectively. Drop-out rate was less than 1%. An increase in the anterior/posterior TTB standard deviation of the minima of the right leg (2.88 ± 0.41, p= 0.05) and a trend in increased postural control for the absolute minimum in the anterior/posterior direction of the right leg (1.47± 0.22 p= 0.09) for Team C were present. However, TTB measures did not change significantly for Teams A, B, or D. Conclusions: The inconsistency among the four teams indicates that this program is feasible and able to increase postural control for certain coaches, but not overall. Factors such as gym schedule, school cancelations, and other unforeseen circumstances might have played a role to reduce compliance and effectiveness of the program.